Real Time Implementation of Model Reference Controller in a Spherical Tank Process (Journal of Basic and Applied Research in Biomedicine, 2022)
In non linear process, control of process parameters is one of the important problems particularly, long dead time and unstable process. In this paper, a Model Reference Controller is   implemented to improve the control performance for a spherical tank level process .The control method is combined with IMC and PD feedback where PD feedback is designed by Maclaurin series. The process dynamics are described by the transfer function model by utilizing the step test technique. Experimental results are furnished to illustrate the effectiveness of the Model Reference controller.